Cranial vault thickness variation and inner structural organization in the StW 578 hominin cranium from Jacovec Cavern, South Africa. Issue 121 (August 2018) - Beaudet, Amélie; Carlson, Kristian J.; Clarke, Ronald J.; de Beer, Frikkie; Dhaene, Jelle; Heaton, Jason L.; Pickering, Travis R.; Stratford, Dominic
Abstract: The Sterkfontein Caves site is one of the richest early hominin fossil localities in Africa. More specifically, the fossiliferous deposits within the lower-lying Jacovec Cavern have yielded valuable hominin remains; prominent among them is the Australopithecus partial cranium StW 578. Due to the fragmentary nature of the braincase, the specimen has not yet been formally assigned to a species. In this context, we employ microtomography to quantify cranial thickness and composition of StW 578 in order to assess its taxonomic affinity. As comparative material, we investigate 10 South African hominin cranial specimens from Sterkfontein (StW 505, Sts 5, Sts 25, Sts 71), Swartkrans (SK 46, SK 48, SK 49) and Makapansgat (MLD 1, MLD 10, MLD 37/38), attributed to either Australopithecus or Paranthropus, as well as 10 extant human and 10 extant chimpanzee crania. Thickness variation in and structural arrangement of the inner and outer cortical tables and the diploë are automatically assessed at regular intervals along one parasagittal and one coronal section. Additionally, topographic cranial vault thickness distribution is visualized using color maps. Comparisons highlight an absolutely and relatively thickened condition of the StW 578 cranial vault versus those of other South African Plio-Pleistocene hominins. Moreover, in StW 578, as well as in the Australopithecus specimens Sts 5 and Sts 71 from Sterkfontein, the diploic layer contributes substantially to cumulative vault thickness (i.e., >60%). Within the comparative sample investigated here, StW 505 and Sts 71 from Sterkfontein Member 4, both attributed to Australopithecus, most closely resemble StW 578 in terms of cranial vault thickness values, tissue proportions, and two- and three-dimensional distributions. Including additional Plio-Pleistocene Australopithecus and Paranthropus crania from South and East Africa in future studies would further help establish morphological variability in these hominin taxa.